The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1242/jcs.131169
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of the EGFR ligand Spitz regulates its signaling activity in polarized tissues

Abstract: SummaryEpidermal growth factor receptor (EGFR) ligands undergo a complex series of processing events during their maturation to active signaling proteins. Like its mammalian homologs, the predominant Drosophila EGFR ligand Spitz is produced as a transmembrane pro-protein. In the secretory pathway, Spitz is cleaved within its transmembrane domain to release the extracellular signaling domain. This domain is modified with an N-terminal palmitate group that tethers it to the plasma membrane. We found that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…A recent report has shown that unprocessed Spi can be observed at the apical surface of the polarized epithelia in the presence of Star, but such Spi is inactive owing to the localization of the receptor in the basal lateral region (Steinhauer et al, 2013). In that report, it is suggested that Spi is endocytosed, cleaved by Rhomboid in endosomes and released to the basal lateral region to activate EGFR signaling (Steinhauer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report has shown that unprocessed Spi can be observed at the apical surface of the polarized epithelia in the presence of Star, but such Spi is inactive owing to the localization of the receptor in the basal lateral region (Steinhauer et al, 2013). In that report, it is suggested that Spi is endocytosed, cleaved by Rhomboid in endosomes and released to the basal lateral region to activate EGFR signaling (Steinhauer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In that report, it is suggested that Spi is endocytosed, cleaved by Rhomboid in endosomes and released to the basal lateral region to activate EGFR signaling (Steinhauer et al, 2013). Alternatively, Spi can potentially enter the Rhomboid-containing endosomes from Golgi and be released to the appropriate location after processing by Rhomboid (Yogev et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the EGFR ligand Spitz is responsible for the signaling between the cells, and that in CAP-D3-deficient cells there might be a defect in Spitz localization. It was recently shown that the localization of transmembrane Spitz to the apical region of imaginal disc cells renders it incapable of activating EGFR in neighboring cells (Steinhauer et al, 2013). Both overexpression of secreted Spitz and knockdown of Argos, which associates predominantly with Spitz to prevent EGFR signaling (Vinos and Freeman, 2000), rescue the loss-of-ACV phenotype in CAP-D3-deficient cells (Fig.…”
Section: Maintenance Of Egfr Activity By Cap-d3mentioning
confidence: 91%
“…It is possible that EGFR is trafficked by distinct routes in imaginal discs and in follicle cells. Grk is internalized through the apical domain of follicle cells (Tanentzapf et al, 2000), whereas active forms of Spi are localized basolaterally in discs (Steinhauer et al, 2013). A role for Vps4 in targeting the EGFR to the appropriate membrane domain would, however, not explain the requirement for Vps4 in cultured S2 cells, which lack apical-basal polarity.…”
Section: Vps4 Might Contribute To Egfr Activationmentioning
confidence: 98%